Program interaktif pengenalan orkestra gamelan di Sekolah Menengah Kebangsaan Kubang Telaga, Bachok - Che Aziz, Che Nur Azira (2015)
The concept study Teaching and Learning (P&P) for the subject of music in Sekolah Menengah Kebangsaan Kubang Telaga, Bachok. The program is produced through interactive cd at the school for the students became active in the persuit of knowledge gamelan music. This study was conducted to form one, two, and three of the 40 respondents who were students of the subjects of music in Sekolah Menengah Kebangsaan Kubang Telaga, Bachok. The method is also done through a questionnaire that includes question related to the use of interactive media at the school. In the formula, the use of interactive media needs to be applied in secondary schools to enables students to understand and learn music ensemble. With this, an interactive CD for teaching and learning, teachers and students can use as reference for the subject music in Sekolah Menengah Kebangsaan Kubang Telaga, Bachok.